Propuesta de mejora para la gestión y control de inventario en la fabricación de Spooler en la empresa SERPET LLANOS S.A.S (2021)
The following is done responding to the problem presented by the Serpet Llanos SAS organization, in which it currently requires strategies to perform an optimal inventory control, which is why, according to the knowledge obtained throughout the professional engineering career an analysis of the current inventory management procedure is performed. Digital tools are provided that promise to make this unit control effective with the help of an office package, classification under the ABC method, and establishing important criteria in relation to the units that must be kept in the EOQ model warehouse in order not to generate delays to the operational area, establishing the importance of evaluating the costs of inputs and developing a dynamic procedure that is timely at the time of provisioning to comply with the operational activities of the organization and subsequently with the clients.